Enhancing efficiency and stability in perovskite solar cells: innovations in self-assembled monolayers - Tian, Jingshu; Zhang, Haichang (Frontiers in Chemistry, 2025)
Perovskite solar cells (PVSCs) show remarkable potential due to their high-power conversion efficiencies and scalability. However, challenges related to stability and long-term performance remain significant. Self-assembled monolayers (SAMs) have emerged as a crucial solution, enhancing interfacial properties, facilitating hole extraction, and minimizing non-radiative recombination. This review examines recent advancements in SAMs for PVSCs, focusing on three key areas: anchoring groups and interface engineering, electronic structure modulation as well as band alignment, and stability optimization. We emphasize the role of anchoring groups in reducing defects and improving crystallinity, alongside the ability of SAMs to fine-tune energy levels for more effective hole extraction. Additionally, co-adsorbed SAM strategies was discussed which can enhance the durability of PVSCs against thermal and moisture degradation. Overall, SAMs present a promising avenue for addressing both efficiency and stability challenges in PVSCs, paving the way toward commercial viability. Future research should prioritize long-term environmental durability and the scaling up of SAM applications for industrial implementation.